(untitled) (Filološke studije, 2019)
The article deals with using metaphor modeling in comparative studies of metaphorization in different discourse types. The comparative analysis is carried out in different types of medical discourse (scientific, popular, nonprofessional) and different forms of language representation (text and associative field) in the Russian, English and German languages.